Author Correction: Effects of Compound Sand Barrier for Habitat Restoration on Sediment Grain-size Distribution in Ulan Buh Desert - Xia Pan (Nature Portfolio, 2020)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.